Pengaruh Konsentrasi Ekstrak Etanolik Daun Teh Hijau (Camellia sinesis L.) dalam Sediaan Krim terhadap Sifat Fisik dan Aktivitas Antibakteri - Widyaningrum, Naniek; Murrukmihadi, Mimiek; Ekawati, Syarifatun Karunia (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2012)
Background: Green tea, is one of the herbs that have been proven to be effective as an anti-acne, among others.Green tea leaves contain 30-40% polyphenols known as catechins most of which are antimicrobial. For ease of use, the ethanolic leaf extract of green tea is made in cream. This study aimed to determine the effect of variations in the concentration of ethanolic extract of green tea leaves in cream on the physical properties and antibacterial activity of acne bacteria in particular.Design and Method: In this study, green tea leaf extract condensed obtained by maceration using 50% ethanol solution. Cream formula that is made in five concentration ethanolic extract of green tea leaves 1%, 3%, 5%, 7%, and 9% use a modified formula antiacne cream. Cream tested physical properties include homogenity, percent separation, dispersive power and adhesion. During the antibacterial activity was also tested. The data obtained were analyzed statistically using the non-parametric Kruskal-Wallis test followed by Mann Whitney test with a level of 95%.Results: The preparation cream ethanolic leaf green tea extract at various concentrations have good homogenity and not separate, the greater concentration of cream ethanolic extract of green tea leaves get smaller power and energy dispersive adhesion, whereas the inhibitory against Staphylococcus aureus bacteria is getting biger. Conclusion: Cream ethanolic extract of green tea leaves that are comparable with the positive control (Ristra acne creaming) the physical properties and the antibacterial activity at a concentration of 7% (Sains Medika, 4(2):147-156).